PENGUATAN KARAKTER PEDULI LINGKUNGAN MELALUI GERAKAN PEDULI DAN BERBUDAYA LINGKUNGAN DI SEKOLAH (PBLHS) - Irma Fitriana Ulfah; Andi Setiawan; Tia Subekti (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
The Environmental Care and Culture Movement in Schools is regulated by the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.52/MENLHK/SETJEN/KUM.1/9/2019. The PBLHS movement is a conscious, voluntary, networked, and sustainable collective action carried out by schools in implementing environmentally friendly behavior. Elementary school is the right level of education for instilling an environmentally caring character, because elementary school is the first level of education that students take formally. This Community Service was carried out at SDN Tunjungsekar 4, Malang City. The purpose of this activity is to build an alpha generation with an environmental character. This activity was carried out by providing socialization of strengthening environmental character to students in grades 1-3, mapping activities that are part of the PBHLS movement carried out by the school, and analyzing obstacles that occurred. The results of the activity show that this movement has been implemented through the Pancasila Student Profile Strengthening Project (P5) which carries the theme of Sustainable Lifestyle. In addition, the school has also carried out habits through daily activities as a habit in building an environmentally caring character.